Analysis of the Implementation of Total Physical Response in Teaching English Listening Skills to Autism Students at SKH Negeri 01 Cilegon - Afifah Nabilah; Yudi Juniardi; Rosmania Rima (Menulis: Jurnal Penelitian Nusantara, 2025)
In recent years, the integration of children with autism into regular classrooms has garnered considerable attention, highlighting the need for effective educational practices tailored to their specific needs. This research aims to enhance English listening abilities in autistic children using the Total Physical Response (TPR) technique in the SMP-C grade at SKH Negeri 01 Cilegon. This research used a qualitative descriptive technique, utilizing observational and participant data to examine the implementation, advantages, and efficacy of Total Physical Response (TPR) in an inclusive classroom environment. The results indicate that Total Physical Response (TPR), which integrates physical activity with verbal guidance, significantly improves students' listening comprehension and memory. This approach is particularly beneficial for autistic learners who react well to tactile and visual stimuli. TPR activities, including gestures, visual aids, practical tasks, and objects, enhance classroom engagement and accommodate varied learning requirements. Students demonstrated enhanced knowledge, increased engagement, and elevated self-confidence, especially among those exhibiting greater collaboration. For students who exhibited reluctance or minimal responsiveness, supporting techniques such as repetition, explicit instructions, and positive reinforcement were crucial in enhancing their involvement. The study emphasizes the difficulties in accommodating diverse student reactions, highlighting the necessity for instructor adaptability, ingenuity, and perseverance. Notwithstanding these limitations, TPR has shown efficacy in enhancing listening abilities and fostering the physical, social, and emotional development of autistic adolescents. In conclusion, TPR provides a comprehensive, learner-centric methodology that enhances the accessibility, engagement, and significance of English language acquisition for children with autism.